The Effects of Applying Apparent Diffusion Coefficient Parameters on the Differentiation between Fourth Ventricular Ependymoma and Diffuse Intrinsic Pontine Glioma - Duc, Nguyen Minh (Journal of Child Science, 2020)
Distinguishing the fourth ventricular ependymoma from diffuse intrinsic pontine glioma (DIPG) is essential to improve the treatment strategy between these two tumor types. We attempted to evaluate the effects of applying apparent diffusion coefficient (ADC) values to the distinction between pediatric fourth ventricular ependymomas and DIPGs. Brain magnetic resonance imaging, including diffusion-weighted imaging and ADC, was assessed in 26 patients, who were divided into two groups: group 1 included 8 patients with fourth ventricular ependymoma and group 2 included 18 patients with DIPG. The Mann–Whitney U test was utilized to compare tumoral maximum (ADCmax), minimum ADC (ADCmin), mean ADC (ADCmean), and standard deviation (ADCsd) values, and the ratios between the tumor and parenchyma values for each of these parameters (rADCmax, rADCmin, rADCmean, and rADCsd, respectively) between the two groups. Cutoff values were calculated based on receiver operating characteristic curve analysis and the Youden index, and the area under the curve (AUC), sensitivity, and specificity were determined. The median ADCmax, ADCmin, ADCmean, rADCmax, rADCmin, and rADCmean values were significantly lower in group 1 than in group 2 (p < 0.05). For the differential diagnosis of ependymomas and DIPGs, a cutoff ADCmean value of 1.02 × 10−3 mm2/s was determined, which produced a sensitivity of 100%, a specificity of 88.9%, and an AUC of 95.8%. ADC parameters should be considered when performing a differential diagnosis between fourth ventricular ependymomas and DIPGs. Based on our findings, a cutoff ADCmean value of 1.02 × 10−3 mm2/s was the most significant and effective parameter for this purpose.
Keywords: fourth ventricular ependymoma; diffuse intrinsic pontine glioma; magnetic resonance imaging; apparent diffusion coefficient